Incorporating STEAM Strategies to Develop Scientific Problem- Solving Skills in Infants - Miguel Angel Ortiz-Esparza; Héctor Cardona-Reyes; David Rondon; Briseida Sotelo-Castro; Klinge Villalba-Condori (CLEI Electronic Journal, 2025)
In infants, teaching strategies focus on play and experiential activities; The development of scientific competencies based on STEAM involves a series of pedagogical approaches, so the purpose of this work was to implement a mini-ecosystem as a teaching strategy. 20 children between 4 and 5 years old from the educational institution “Dulces Brotecitos” participated. The study is developed within the qualitative paradigm, as a case study over a period of 2 months for the operation of the mini-ecosystem and 3 months for its implementation. Non- participant observation, recording of photos and videos were used; and field notebook to analyse the results.